Building Readiness to Change in Organization through the Role of Affective Commitment and Personal Characteristics - Suharmanto Suharmanto; Iwan Hermawan; Inayah Inayah; Asti Khoerunisa (Research Synergy Foundation, 2024)
Human Capital as an intangible asset is the key to building Readiness for Change (RTC), which is rooted in Self-Efficacy (SE) and Job Satisfaction (JS), which in several previous studies were not significant. Human capital refers to the role of Individuals as important agents in organizations based on the existence of Personal Characteristics (PC) that facilitate the achievement of SE and JS to improve RTC. The purpose of the study is to offer Affective Commitment (AC) as mediating variable in the nexus between SE and JS. This study uses a quantitative approach with 124 school principals in Indonesia, employing Structural Equation Modeling (SEM) to examine Affective Commitment (AC) in bridging the gap between SE and JS on RTC. The results of empirical testing using SEM instruments processed with AMOS software show that AC can fully mediate JS (B= 0.614) on the RTC. However, AC utilizes only part of SE (B= 0.390) in the RTC. This finding confirms that the best path to building an RTC through PC strengthening is through JS and AC. The principal, in their capacity as an organizational leader, holds a pivotal role in cultivating an environment conducive to fostering self-efficacy (SE) and establishing a cohesive, innovative atmosphere that emphasizes the influence of personal character on job satisfaction. Moreover, it is imperative for the principal to advocate for continuous enhancement of knowledge and expertise through structured training, autonomous learning, and collaborative knowledge-sharing practices. This finding contributes to the body of knowledge in the perspective of commitment from Human Capital.